Regulasi dan Lisensi Mengenai Perlindungan Hukum Investor di Platform Fintech Peer-To-Peer Lending dalam Hukum Konvensional - Seri Mughni Sulubara; Iskandar Iskandar (Pusat Riset dan Inovasi Nasional, 2025)
Peer-to-Peer (P2P) Lending is a financing model that connects lenders with borrowers directly through a digital platform, without the intermediary of banks or traditional financial institutions. Fintech P2P Lending is regulated in the Financial Services Authority Regulation Number 77/POJK.01/2016. The purpose of the research is to find out the regulations and licenses regarding the legal protection of investors in peer-to-peer lending fintech platforms in conventional law. The research method used is normative legal research that examines applicable regulations related to fintech P2P lending in conventional law. The legal basis of regulations and licenses regarding the legal protection of investors in peer-to-peer lending (P2PL) fintech platforms in Indonesia is OJK Regulation No. 77/POJK.01/2016. Law Number: 19/2016 on the Amendment to Law Number 11/2008 on Electronic Information and Transactions, which is stated in Article 26 paragraphs (1) and (2). This regulation has given consumers the right as owners of personal data to maintain the confidentiality of their personal data. Article 28 paragraphs (2) and (3) of Law Number 21 of 2011 concerning the Financial Services Authority, OJK has the authority to request financial services institutions to stop their activities if they are detrimental to the community and carry out other actions deemed necessary and in accordance with laws and regulations in the financial services sector.